Myth of the Inferior Status of Vocational Education: The Case of Hong Kong. Issue 6 (2nd November 2018) - Yau, Thomas Siu Ho; Chung, Ming Lun; Li, Ho Ching; Chun, Derek Wai Sun
Abstract: In this article, factors contributing to the poor perceptions and inferior status of vocational education in Hong Kong are discussed. Critical discourse analysis (CDA) is employed as the methodology in examining the discursive construction of vocational education in the policy context. A total of five policy documents published between 1970 and 2015 are included. Our findings show that the socioeconomic transformation of Hong Kong in recent decades, massification of higher education, and cultural factors such as parental expectations are pertinent to the stigmatization observed in vocational education. This article discusses the implications from the findings and concludes with possible solutions for the future development of vocational education in Hong Kong under the novel vocational and professional education and training (VPET) initiative launched by the government.